2011
DOI: 10.1037/a0020873
|View full text |Cite
|
Sign up to set email alerts
|

Older adults' configural processing of faces: Role of second-order information.

Abstract: Problems with face recognition are frequent in older adults. However, the mechanisms involved have only been partially discovered. In particular, it is unknown to what extent these problems may be related to changes in configural face processing. Here, we investigated the face inversion effect (FIE) together with the ability to detect modifications in the vertical or horizontal second-order relations between facial features. We used a same/different unfamiliar face discrimination task with 33 young and 33 olde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(59 citation statements)
references
References 58 publications
4
54
1
Order By: Relevance
“…Compared with younger adults, older adults are less likely to look at someone’s eyes and more likely to look at their mouth or nose (Circelli et al, 2013, Firestone et al, 2007, Heisz and Ryan, 2011, Murphy and Isaacowitz, 2010, Sullivan et al, 2007, Wong et al, 2005) and are worse than younger adults at detecting configural changes in the eye region than in the mouth/nose region of the face (Chaby et al, 2011, Slessor et al, 2013). The age difference in top-bottom bias is seen for both neutral and emotional faces but not for scenes (Circelli et al, 2013).…”
Section: Relations Between Emotional Processing In Aging and Brain Fumentioning
confidence: 99%
“…Compared with younger adults, older adults are less likely to look at someone’s eyes and more likely to look at their mouth or nose (Circelli et al, 2013, Firestone et al, 2007, Heisz and Ryan, 2011, Murphy and Isaacowitz, 2010, Sullivan et al, 2007, Wong et al, 2005) and are worse than younger adults at detecting configural changes in the eye region than in the mouth/nose region of the face (Chaby et al, 2011, Slessor et al, 2013). The age difference in top-bottom bias is seen for both neutral and emotional faces but not for scenes (Circelli et al, 2013).…”
Section: Relations Between Emotional Processing In Aging and Brain Fumentioning
confidence: 99%
“…Surprisingly, relatively few studies have explored the possibility that perceptual factors might explain facial emotion recognition difficulties in healthy aging (Orgeta and Phillips, 2007), in spite of many studies indicating age-related changes in visual perception (Bian and Andersen, 2008; Andersen, 2012), especially in face processing (Firestone et al, 2007; Habak et al, 2008; Chaby et al, 2011; Konar et al, 2013). In particular, we showed in a previous study that aging affects some aspects of configural face-encoding processes (e.g., older adults were worse than younger adults at detecting configural changes in the eye region of the face only, but not in the nose–mouth region) which could be related to problems with face recognition (Chaby et al, 2011); see also (Slessor et al, 2013; Meinhardt-Injac et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In an ERP study of neural adaption, Eimer, Gosling, Nicholas, and Kiss (2011) found (with young participants) that inverting schematic faces does not necessarily disrupt all configural processing of schematic faces by showing similar decreases in the face-sensitive N170 ERP component following photographic, upright schematic and inverted schematic faces. There is also evidence that face inversion is not sufficient to disrupt older participants' recognition of photographic faces (Chaby, Narme, & George, 2011). Thus, it is likely that older adults were using some preserved configural emotional processing from the faces that allowed them to recognize and tag (across trials) negative emotions.…”
Section: Discussionmentioning
confidence: 99%